Influence of process water recirculation on hydrothermal carbonization of rice husk at different temperatures. Issue 2 (April 2023) - Ding, Yan; Li, Debo; Lv, Maochao; Yuan, Longji; Zhang, Jing; Qin, Shiru; Wang, Baosu; Cui, Xin; Guo, Chuwen; Zhao, Peitao
Abstract: This work targets to study the influence of PW recirculation on hydrochars at 180, 220, and 260 ℃. Rice husk was hydrothermal carbonized for 1 h and PW was cycled 5 times. The results showed that PW recirculation improved the mass yield and energy recovery efficiency (ERE) of hydrochars. With the increase of temperature, the mass yield of hydrochars decreased and ERE increased first and then decreased. PW recirculation promoted the increase of carbon content at 180 and 220 ℃. When the temperature increased, the carbon content increased, while the hydrogen and oxygen content decreased. The high heating value (HHV) increased with the increase of PW recirculation and temperature. At 180 and 220 ℃, the fixed carbon increased with the increase of PW recirculation and temperature. SEM analysis showed that PW recirculation promoted the formation of carbon microspheres. At 260 ℃, carbon microsphere fusion occurred. After recirculation, the ignition temperature and burning temperature of hydrochars decreased. The aromatic vibration (CC) intensified after the PW recirculation, indicating the occurrence of aromatization and polymerization. Overall, PW recirculation could improve the hydrothermal carbonization process to a certain extent. Graphical Abstract: ga1 Highlights: PW recirculation could promote the formation of hydrochars at 180, 220, and 260 ℃. The MY of hydrochars increased by 3.98% (180 ℃), 8.11% (220 ℃) and 4.44% (260 ℃). The ERE of hydrochars increased by 13.18% (180 ℃), 18.58% (220 ℃) and 19.62% (260 ℃). Compared with 180 ℃ and 260 ℃, 220 ℃ was a more suitable temperature for HTC. PW recirculation could promote the formation of microparticles on surfaces of hydrochars.